E-formalizm procedur jurysdykcyjnych w perspektywie zasady zaufania do władzy publicznej .......... 265 - Grzybowski, Tomasz; Jaśkiewicz, Jacek (E-administracja: Wyzwania dla cyfrowych usług publicznych w Unii Europejskiej, 2024)
E-FORMALISM OF JURISDICTIONAL PROC EDURES IN THE PERSPECTIVE OF THE PRINCIPLE OF TRUST IN PUBLIC AUTHORITYMost of the procedures functioning in the legal system are jurisdictional procedures, aimed at authoritative, unilateral determination of the legal situation of an individual. The general administrative procedure regulated by the Code is a perfect example of such a procedure. An inherent feature of the normative perspective assumed by the procedures of the above-mentioned is procedural formalism, which is also an attractive approach in the field of applying the law, due to the goals of speed, efficiency and conclusiveness of proceedings pursued in this way. The indicated goals are also implemented through the digitization of communication methods, i.e. incorporating elements related to the use of information technology into the procedures. Increased digitization of administrative procedures brings undoubted benefits in the form of improved communication, acceleration and increased certainty of the transmitted data and documents. In some situations, however, it may lead to limiting access to public authority, especially when formal conditions for examining the case by a public administration body depend on its proper use. From the citizen’s point of view, digitization can therefore be perceived as another barrier in communication with the state. In this perspective, the general principle of trust comes to the fore as a criterion for assessing the acceptable limit of formalism in the application of procedural solutions assuming electronic communication with a citizen.